Shape factor effect of radiative Cu-Al2O3/H2O hybrid nanofluid flow towards an EMHD plate - Khashi'ie, Najiyah Safwa; Md Arifin, Norihan; Sheremet, Mikhail; Pop, Ioan (Elsevier, 2021)
This paper aims to analyze the effects of different nanoparticles shape factor, EMHD and radiation parameters for the Cu–Al2O3/H2O nanofluid flow towards a stretching/shrinking Riga plate. The model is simplified into a set of ordinary (similarity) differential equations using the similarity transformation while the existing correlations are used to estimate the thermophysical properties for Cu–Al2O3/H2O. The comparison with previous results is in a good agreement with 0% error. Second solution is found and only exist in certain value of the shrinking parameter which reflects the unstableness of the solution. From the streamlines plot, the second solution dislocates the stagnation line far away from the wall surface to the reverse flow region as compared to the first solution. An increase of 1% EMHD parameter extends the separation value by 0.4%. This reflects the potential of EMHD parameter in delaying the separation process. Further, the heat transfer rate slightly increases with the rise of EMHD, radiation and shape factor parameters. The maximum heat transfer rate is acquirable for the ascendance nanoparticle concentration using blade-shape while the sphere-shape produce the lowest thermal rate. These findings are important in long run where we can plan for the heat transfer optimization of the cooling/heating applications.